Bronchitis in Children Prevention and Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Bronchitis in children is an acute, subacute, or chronic inflammatory disease of the lower respiratory tract, specifically the bronchi. In the vast majority of cases, the inflammation is purely infectious in nature, although other pathological causes are also encountered in some situations. The disorder is accompanied by pronounced clinical symptoms: difficulty breathing, chest pain, and signs of general intoxication, including fever, unless allergic inflammation is also common.